1995
DOI: 10.3354/meps119025
|View full text |Cite
|
Sign up to set email alerts
|

Otolith strontium traces environmental history of subyearling American shad Alosa sapidissima

Abstract: Sagittal otoliths of young-of-year American shad Alosa sapidjssirna from the Hudson River estuary, New York, USA, were transected with an X-ray-dispersive microprobe to examine temporal patterns of strontium, a micro-constituent found in otolith aragonite. Otoliths were assayed from fish reared on known diets (freshwater zooplankton, followed by artificial diet containing marine fishmeal) in fresh water. The switch from freshwater plankton to artificial diet resulted in a significant rise in Sr:Ca ratio in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
152
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(160 citation statements)
references
References 5 publications
8
152
0
Order By: Relevance
“…The usefulness of natural biogeochemical tags derived from calcified structures stems from the relationship between water chemistry, other environmental factors and element : Ca ratios in the structures themselves. Under estuarine conditions, bony fish otolith Sr : Ca generally shows a positive correlation with salinity, whereas Ba : Ca typically shows a negative relationship with salinity (Limburg 1995;Elsdon and Gillanders 2005;Macdonald and Crook 2010). Because a large portion of otolith Sr and Ba is derived from the surrounding water (Walther and Thorrold 2006;Webb et al 2012;Izzo et al 2015), fluctuations in Sr : Ca and Ba : Ca can be used to infer the relative salinity of environments experienced by a fish during its lifetime (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of natural biogeochemical tags derived from calcified structures stems from the relationship between water chemistry, other environmental factors and element : Ca ratios in the structures themselves. Under estuarine conditions, bony fish otolith Sr : Ca generally shows a positive correlation with salinity, whereas Ba : Ca typically shows a negative relationship with salinity (Limburg 1995;Elsdon and Gillanders 2005;Macdonald and Crook 2010). Because a large portion of otolith Sr and Ba is derived from the surrounding water (Walther and Thorrold 2006;Webb et al 2012;Izzo et al 2015), fluctuations in Sr : Ca and Ba : Ca can be used to infer the relative salinity of environments experienced by a fish during its lifetime (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because a large portion of otolith Sr and Ba is derived from the surrounding water (Walther and Thorrold 2006;Webb et al 2012;Izzo et al 2015), fluctuations in Sr : Ca and Ba : Ca can be used to infer the relative salinity of environments experienced by a fish during its lifetime (e.g. Limburg 1995). Similarly, Scharer et al (2012) reported that the Sr : Ca in vertebral sections of the smalltooth sawfish (Pristis pectinata) had a positive correlation with salinity, and Smith et al (2013) reported that the Ba : Ca in the vertebrae of round stingray (Urobatis halleri) was correlated with Ba in seawater.…”
Section: Discussionmentioning
confidence: 99%
“…Element composition of biogenic aragonites is thought to depend mainly on physicochemical properties of the surrounding water (Campana 1999). Nevertheless, it has been repeatedly reported that endogenous factors such as diet might have an eVect on the element compositions of Wsh otoliths (Limburg 1995;Farrell and Campana 1996;Gallahar and Kingsford 1996;Buckel et al 2004) as well as cephalopod statoliths (Zumholz et al 2006), since cations entering the inner ear endolymph via the blood circuit can originate either from branchial or intestinal uptake (Campana 1999). Previous investigations on the importance of food on element incorporation into otoliths were highly ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Walther and Thorrold (2006) concluded that Sr and Ba contents in marine Wsh otoliths clearly reXect ambient Sr and Ba concentrations, while Kennedy et al (2000) reported 70% of the Sr isotopic signature in freshwater Atlantic salmon (Salmo salar) otoliths to originate from food. SigniWcant dietary eVects on strontium incorporation have been demonstrated for American shad (Alosa sapidissima) (Limburg 1995) and Black bream (Girella elevata) (Gallahar and Kingsford 1996) and for strontium and barium incorporation in blueWsh (Pomatomus saltatrix) (Buckel et al 2004). No eVects were detected for the uptake of magnesium, potassium, strontium, sodium, and calcium in Red drum (Sciaenops ocellatus) (HoV and Fuiman 1995), for strontium, copper and lead in barramundi (Milton and Chenery 2001), for sodium, magnesium, potassium, calcium and manganese in blueWsh (P. saltatrix) (Buckel et al 2004) and for strontium in Japanese eel (Anguilla japonica) (Lin et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Arai et al 2004;Limburg 1995Limburg , 1996Limburg , 1998Campana et al 2000; for a comprehensive review see : Campana 1999). Compared to fish otoliths, there have been only few studies examining the chemical composition of cephalopod statoliths (e.g.…”
Section: Introductionmentioning
confidence: 99%